The case for food system knowledge support system (FS-KSS) - Ulimwengu, John M.; Mutyasira, Vine; Keizire, Boaz (Alliance for a Green Revolution in Africa, 2025)
The Comprehensive Africa Agriculture Development Programme (CAADP) Strategy and Action Plan (2026-2035) is a key framework aimed at transforming Africa’s agrifood systems to achieve sustainable agricultural growth, food security, and economic development across the continent. Building on the lessons from the Malabo Declaration, the Plan emphasizes the need for sustainable food production, inclusivity, and resilience in the face of climate change and other challenges. However, achieving these ambitious goals requires a robust and integrated support system that can provide accurate, real time data, facilitate evidence-based decision-making, and promote accountability among stakeholders. Without a well-functioning knowledge system, the efforts to transform agrifood systems may be hindered by data gaps, limited analytical capacity, and a lack of coordination among various actors. The effectiveness of food systems in Africa is often hindered by data gaps, inconsistencies, and limited capacity for data analysis. These issues compromise the ability of governments and other stakeholders to make informed decisions, implement sound policies, and monitor progress toward national and continental goals such as food security and climate resilience. This is where the Food System Knowledge Support System (FS-KSS) becomes crucial, as it provides the necessary tools to ensure effective implementation of the CAADP Strategy and Action Plan.